Endothelial Dicer promotes atherosclerosis and vascular inflammation by miRNA-103-mediated suppression of KLF4 - Hartmann, Petra (Nat Commun, 2016)
MicroRNAs regulate the maladaptation of endothelial cells (ECs) to naturally occurring disturbed blood flow at arterial bifurcations resulting in arterial inflammation and atherosclerosis in response to hyperlipidemic stress. Here, we show that reduced endothelial expression of the RNAse Dicer, which generates almost all mature miRNAs, decreases monocyte adhesion, endothelial C–X–C motif chemokine 1 (CXCL1) expression, atherosclerosis and the lesional macrophage content in apolipoprotein E knockout mice (Apoe(−/−)) after exposure to a high-fat diet. Endothelial Dicer deficiency reduces the expression of unstable miRNAs, such as miR-103, and promotes Krüppel-like factor 4 (KLF4)-dependent gene expression in murine atherosclerotic arteries. MiR-103 mediated suppression of KLF4 increases monocyte adhesion to ECs by enhancing nuclear factor-κB-dependent CXCL1 expression. Inhibiting the interaction between miR-103 and KLF4 reduces atherosclerosis, lesional macrophage accumulation and endothelial CXCL1 expression. Overall, our study suggests that Dicer promotes endothelial maladaptation and atherosclerosis in part by miR-103-mediated suppression of KLF4.